Commodity risk assessment of Prunus spp. plants from United Kingdom - EFSA Panel on Plant Health (PLH); Antonio Vicent Civera; Paula Baptista; Elisavet Chatzivassiliou; Jaime Cubero; Nik Cunniffe; Eduardo de laPeña; Nicolas Desneux; Anna Filipiak; Paolo Gonthier; Beata Hasiów‐Jaroszewska; Hervé Jactel; et al. (EFSA Journal, 2025)
Abstract The European Commission requested the EFSA Panel on Plant Health to prepare and deliver risk assessments for commodities listed in Commission Implementing Regulation (EU) 2018/2019 as ‘High risk plants, plant products and other objects’. This Scientific Opinion covers plant health risks posed by: grafted potted plants up to 15 years old or bundles of grafted bare root plants up to 3 years old or graftwood up to 2 years old of Prunus armeniaca, P. cerasifera, P. domestica, P. incisa or P. persica imported from the United Kingdom (UK), taking into account the available scientific information, including the technical information provided by the UK. All pests associated with the commodities were evaluated against specific criteria for their relevance for this opinion. Two quarantine pests, Candidatus Phytoplasma aurantifolia‐related strains (Pear decline Taiwan II, Crotalaria witches' broom phytoplasma, Sweet potato little leaf phytoplasma) and Scirtothrips dorsalis, two protected zone quarantine pests, Bemisia tabaci (European population) and Erwinia amylovora, and two non‐regulated pests, Eulecanium excrescens and Colletotrichum aenigma, that fulfilled all relevant criteria were selected for further evaluation. The risk mitigation measures proposed in the technical Dossier from the UK were evaluated, taking into account the possible limiting factors. For these pests, expert judgement is given on the likelihood of pest freedom, taking into consideration the risk mitigation measures, including uncertainties associated with the assessment. The degree of pest freedom varied among the pests evaluated, with E. amylovora being the most frequently expected pest on the imported potted plants. The expert knowledge elicitation indicated with 95% certainty that between 9956 and 10,000 potted plants per 10,000 would be free from the above‐mentioned bacterium.